2005
DOI: 10.1002/cncr.21549
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin β (HCGβ) down‐regulates E‐cadherin and promotes human prostate carcinoma cell migration and invasion

Abstract: People are not equally disabled by combined anterior cruciate ligament (ACL)/medial collateral ligament (MCL) injuries, nor do they all develop osteoarthritis (OA). Although biological/biomechanical causes are not clear, some association presumably exists between joint instability and OA development. We hypothesized that degree of OA development following standardized complete ACL/MCL injuries will vary directly with the degree of biomechanical abnormality between individuals. Three groups of sheep were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Down-regulation or loss of E-cadherin has been implicated in the gain of invasive potential by carcinomas (34)(35)(36)(37). h-Catenin also functions as a component of adherent cell-cell junctions that promote cell adhesion by binding to the intracellular domain of E-cadherin and linking E-cadherin to the cytoskeleton through the adaptor Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation or loss of E-cadherin has been implicated in the gain of invasive potential by carcinomas (34)(35)(36)(37). h-Catenin also functions as a component of adherent cell-cell junctions that promote cell adhesion by binding to the intracellular domain of E-cadherin and linking E-cadherin to the cytoskeleton through the adaptor Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a reversible process, whereby the epithelial cells lose their junctions and polarity, reorganize their cytoskeleton, gain ability of motility, transit into mesenchymal cells and develop an invasive phenotype (30). The functional loss of E-cadherin is the typical characteristic of EMT and this contributes to the destabilization of adheren junctions, as well as tumor invasion and metastasis (20,30,47,48). Therefore, SFN is capable of suppressing the process of EMT by inducing E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the inhibitory effect of the prostate cancer cell invasion was mediated via restoration of Ecadherin expression [15]. In previous studies, it was suggested that inactivation of E-cadherin was one of the main characteristics of metastatic prostate cancer [16][17][18][19]. Chu et al showed that E-cadherin expression was induced by the garlic derivatives in some other human cancer cell lines including ovarian, nasopharyngeal and esophageal cancer cell lines [15].…”
Section: Cell Line Studiesmentioning
confidence: 95%